2017
DOI: 10.1080/03009734.2017.1405127
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-based recall to study metabolic effects of genetic variation: a pilot study ofPPARGPro12Ala carriers

Abstract: AimTo assess practical implications of genotype-based recall (GBR) studies, an increasingly popular approach for in-depth characterization of genotype–phenotype relationships.MethodsWe genotyped 2500 participants from the Swedish EpiHealth cohort and considered loss-of-function and missense variants in genes with relation to cardiometabolic traits as the basis for our GBR study. Therefore, we focused on carriers and non-carriers of the PPARG Pro12Ala (rs1801282) variant, as it is a relatively common variant wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…After rare variant genotype calling with zCall version 3.3 (https://github.com/jigold/zCall), markers with a call rate <99% or a Fisher’s exact test p value for Hardy–Weinberg equilibrium <10 −4 were also excluded. Further details can be found in the study by Kamble et al [17]. In total, 2432 samples passed quality control, and 2378 samples remained after further exclusion of related individuals.…”
Section: Methodsmentioning
confidence: 99%
“…After rare variant genotype calling with zCall version 3.3 (https://github.com/jigold/zCall), markers with a call rate <99% or a Fisher’s exact test p value for Hardy–Weinberg equilibrium <10 −4 were also excluded. Further details can be found in the study by Kamble et al [17]. In total, 2432 samples passed quality control, and 2378 samples remained after further exclusion of related individuals.…”
Section: Methodsmentioning
confidence: 99%
“…The gene expression analysis using PCR is often influenced by the choice of housekeeping genes and therefore we acknowledge that if genes other than 18S rRNA or GUSB were used, this might possibly modify the results slightly. In addition, the number of subjects included was small due to a limited number of subjects to invite, in particular within the Ala/Ala group, and the participation rate was reduced by the extensive investigation.- 35 This decreased the probability of finding statistically significant differences, especially when studying a common variant like Pro12Ala with an effect size of a modest magnitude. However, based on power calculations, a comparison of two groups with the current sample sizes allowed 80% power to detect a 20% difference in insulin action on adipocyte lipolysis as well as on glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…As our narrative review shows, the literature on GBR studies as applied to cardiometabolic health outcomes is expanding but remains small. Most existing GBR studies are descriptive in nature 4, 811, 1315, 20 , having used recall to minimize the sample size required to deploy bespoke phenotyping methods; a handful of additional GBR studies have examined gene-drug or gene-diet interactions 12, 1719, 24, 25 ; and only one GBR study has incorporated MR to enhance causal inference 26 , whilst one further study combined GBR and gene-editing technologies to study mechanism of action 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of GBR have looked to assess the causal impact of specific risk factors and also to enhance trial design through informed participant selection 2, 3 . More than a dozen GBR studies focusing on cardiometabolic traits have been reported in the past two decades 420 with contrasting genetic characteristics, with the PPARG Pro12Ala variant (rs1801282) being the single most extensively studied locus.…”
Section: Overview Of Published Gbr Studiesmentioning
confidence: 99%